MicroRNA‐494 Activation Suppresses Bone Marrow Stromal Cell‐Mediated Drug Resistance in Acute Myeloid Leukemia Cells. Issue 6 (19th October 2016) - Tian, Chen; Zheng, Guoguang; Zhuang, Hongqing; Li, Xubin; Hu, Dongzhi; Zhu, Lei; Wang, Tengteng; You, Mingjian James; Zhang, Yizhuo
Abstract : Acute myeloid leukemia (AML) is not sensitive to chemotherapy partially because of the protection of AML cells by mesenchymal stromal cells (MSCs). Our previous studies found that MSCs protected AML cells from apoptosis through the c‐Myc‐dependent pathway. However, the mechanism by which MSCs regulate c‐Myc in AML cells is still unknown. To elucidate the mechanism, we performed microRNA array analysis of AML cell lines and validated by TaqMan realtime PCR. The results showed that the expression of microRNA‐494 (miR‐494) in AML cells after coculture with MSCs was downregulated. Reporter gene analysis confirmed miR‐494 as one of the regulators of c‐Myc. In the coculture system, activation of miR‐494 in AML cells suppressed proliferation and induced apoptosis of AML cells in vitro. After addition of mitoxantrone to the coculture system, the proliferation of AML cells with miR‐494 activation was suppressed more than that of control cells. After subcutaneous injection of AML cell lines in combination with MSC, tumor growth was suppressed in mice injected with miR‐494‐overexpressing AML cells. The rate of tumor formation was even lower after mitoxantrone treatment in the miR‐494 overexpressing group. Moreover, miR‐494 activation resulted in a decrease of leukemic cell counts in peripheral blood (PB) and bone marrow, and prolonged survival in mice injected with miR‐494‐overexpressing AML cellls and MSCs compared to the control mice. Our results indicate that miR‐494 suppresses drug resistance in AML cells by downregulating c‐Myc through interaction with MSCs and that miR‐494 therefore is a potential therapeutic target. J. Cell. Physiol. 232: 1387–1395, 2017. © 2016 Wiley Periodicals, Inc. Abstract : miR‐494 suppresses drug resistance in AML cells by downregulating c‐Myc through interaction with MSCs and that miR‐494 therefore is a potential therapeutic target.